Peanut Consumption and Risk of Stroke and Ischemic Heart Disease in Japanese Men and Women: The JPHC Study. Issue 11 (9th September 2021) - Ikehara, Satoyo; Iso, Hiroyasu; Kokubo, Yoshihiro; Yamagishi, Kazumasa; Saito, Isao; Yatsuya, Hiroshi; Kimura, Takashi; Sawada, Norie; Iwasaki, Motoki; Tsugane, Shoichiro; ,
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: Several prospective cohort studies and a randomized clinical trial have shown the beneficial effects of peanut consumption on cardiovascular disease and its risk factors. We examined the association between peanut consumption and risk of cardiovascular disease in Japanese men and women. Methods: We analyzed data of 74 793 participants aged 45 to 74 years who completed a lifestyle questionnaire including the validated food frequency questionnaire in the Japan Public Health Center–based Prospective Study. They were followed up from 1995 to 2009 for cohort I and from 1998 to 1999 to 2012 for cohort II. Peanut consumption was calculated from the food frequency questionnaire, and the end points were incidence of stroke, ischemic heart disease, and cardiovascular disease (stroke and ischemic heart disease). Results: During a median follow-up of 14.8 years, 3, 599 strokes and 849 ischemic heart diseases were reported. Higher peanut consumption was associated with reduced risks of total stroke, ischemic stroke, and cardiovascular disease among men and women. The multivariable hazard ratios (95% CIs) for the highest versus lowest quartiles of peanut consumption after adjustment for age, sex, public health center, smoking, alcohol consumption, perceived stress level, physical activity, vegetable, fruit, fish, soy, sodium and total energy intakes, body mass index, history of hypertension, history of diabetes, and cholesterol-lowering drug were 0.84 (0.77–0.93, P for trend=0.002) for total stroke, 0.80 (0.71–0.90, P for trend=0.002) for ischemic stroke, 0.93 (0.79–1.08, P for trend=0.27) for hemorrhagic stroke, 0.97 (0.80–1.17, P for trend=0.81) for ischemic heart disease and 0.87 (0.80–0.94, P for trend=0.004) for cardiovascular disease, and these associations were similarly observed in both sexes. Conclusions: Higher peanut consumption was associated with reduced risk of stroke, especially ischemic stroke, but not ischemic heart disease in Japanese men and women.